Stellar halos tracing the assembly of ultra-faint dwarf galaxies - Querci, Lapo; Pallottini, Andrea; Branca, Lorenzo; Salvadori, Stefania (Astronomy and astrophysics, 2025)
Methods. We developed N-body simulations of dry isolated mergers between two UFDs, resolving their stellar component down to 1 M . We built a suite of simulations by varying: the merger-speciﬁc i) angular momentum, l, and ii) kinetic energy k, iii) the merger mass ratio, M1/M2, iv) the dark-to-stellar mass ratio, MDM/M?, of the progenitors, and v) their stellar size, R1/2. To fully explore such a ﬁve-dimensional parameter space, we trained a neural network to emulate the properties of the resulting “post-merger” UFD, by quantifying the half-mass radius (R?) and the fraction of stars at radii >5R? ( f5). - Results. Our principal component analysis clearly shows that f5 (R?) is primarily determined by M1/M2 (R1/2), with R1/2 (M1/M2) playing a secondary role. Both f5 and R? show almost no dependence on k, l, and MDM/M? in the explored range. Using our emulator, we ﬁnd that to form the stellar halo observed in Tucana II; that is, f5 = 10 ± 5% and R? = 120 ± 30 pc, we need to merge progenitors with M1/M2 = 8+4 −3, the size of the more massive one being R1/2 = 97+25 −18 pc. Such ﬁndings are corroborated by the consistency (χ2 ' 0.5−2) between stellar density proﬁles observed for Tucana II and those of simulations that have M1/M2 and R1/2 close to the values predicted by the emulator. - Conclusions. The stellar halos of UFDs contain crucial information about the properties of their smaller progenitor galaxies. Ongoing and planned spectroscopic surveys will greatly increase the statistics of observed stars in UFDs, and thus of their associated stellar halos. By interpreting such observations with our simulations, we will provide new insights into the assembly history of UFDs, and thus the early galaxy formation process.
Gesehen am 28.08.2025